2003
DOI: 10.1038/sj.cgt.7700620
|View full text |Cite
|
Sign up to set email alerts
|

A DNA vaccine expressing tyrosinase-related protein-2 induces T-cell-mediated protection against mouse glioblastoma

Abstract: A mouse glioblastoma cell line, termed GL261, was shown to express high levels of proteins involved in melanin biosynthesis such as the tyrosinase-related protein-2 (TRP-2), which is commonly overexpressed in melanoma cells. Mice injected with GL261 cells developed a CD8 + T-cell response to TRP-2 and a DNA vaccine expressing human (h)TRP-2 induced CD8 + T cells that recognized TRP-2 expressed by GL261 cells indicating that this melanoma-associated antigen may be suited for active immunotherapy of glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this study, we used intratumoral administration of G207 to vaccinate mice harboring a syngenic mouse glioma cell line, GL261, which is widely used for the study of immunotherapy against brain tumors [38][39][40][41]. We applied a modified SEREX method to the mouse glioma GL261 model in an attempt to identify molecular therapeutic targets for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used intratumoral administration of G207 to vaccinate mice harboring a syngenic mouse glioma cell line, GL261, which is widely used for the study of immunotherapy against brain tumors [38][39][40][41]. We applied a modified SEREX method to the mouse glioma GL261 model in an attempt to identify molecular therapeutic targets for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that solid tumours were observed at all argues in favour of an insufficient immune response merely delaying or retarding tumour growth. Others have reported long-term survival in a murine brain tumour model following DNA vaccination [12]. The effect of vaccination and reduced tumour growth on suvival time was not investigated in our model.…”
Section: Discussionmentioning
confidence: 95%
“…In some studies with DNA vaccines in knock-out mice, the simultaneous presence of CD4 + and CD8 + cells is necessary [40][42]. However, one study with a vaccine based on vaccinia virus showed requirement for CD4 + cells [43], while another with an adenovirus-based vaccine showed dependence on CD8 + cells [44].…”
Section: Discussionmentioning
confidence: 99%